Multicultural Education in Islamic Boarding School - Harun Rasyid; Ahmad Bisyri Abd.Shomad; Hidayatulloh Hidayatulloh; Kamarusdiana Kamarusdiana; Syamsul Yakin (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2022)
AbstractMulticultural education is crucial in the socio-multicultural atmosphere. Multicultural education encourages students to respect those whose beliefs differ from their own—living in a diverse group of people with the principle that differences are a gift. The method used in this research is qualitative by focusing the design on source triangulation, which analyzes the references from the Qur’an and scholars’ and experts’ ijtima’. This study explored the model of multicultural education practiced by Al-Asyriah Nurul Iman Islamic boarding school in Bogor; It involved stakeholders from students, teachers, and other academic communities. The socio-multicultural values that exist, including ta’aruf, tawasuth, tasamuh, ta’awun, tawazun, peace, and religious freedom, are the foundation of the pesantren education model at the educational institution Bogor. Understanding socio-multiculturalism brings peace and reduces the possibility of social discrimination, violence, and injustice caused mainly by cultural differences in religion, race, ethnicity, language, gender, age, and social strata. AbstrakPendidikan multikultural sangat penting dalam atmosfir sosio-multikultural. Pendidikan multikultural mendorong siswa untuk menghormati mereka yang keyakinannya berbeda dari mereka sendiri—hidup dalam kelompok orang yang beragam dengan prinsip bahwa perbedaan adalah anugerah. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan memfokuskan desain pada triangulasi sumber, yaitu menganalisis referensi dari para ulama dan ahli dari al-Qur’an dan ijtima’. Penelitian ini mengeksplorasi model pendidikan multikultural yang dipraktikkan pesantren Al-Asyriah Nurul Iman Islamicdi Bogor; Melibatkan pemangku kepentingan dari siswa, guru, dan civitas akademika lainnya. Nilai-nilai sosial multikultural yang ada, antara lain ta’aruf, tawasuth, tasamuh, ta’awun, tawazun, damai, dan kebebasan beragama, menjadi landasan model pendidikan pesantren di lembaga pendidikan Bogor. Pemahaman sosio-multikulturalisme membawa perdamaian dan mengurangi kemungkinan diskriminasi sosial, kekerasan, dan ketidakadilan yang disebabkan terutama oleh perbedaan budaya, agama, ras, suku, bahasa, jenis kelamin, usia, dan strata sosial.How to Cite: Rasyid, H, Shomad, A. B. A., Hidayatulloh, Kamarusdiana, Yakin, S. (2022). Multicultural Education in Islamic Boarding School. TARBIYA: Journal of Education in Muslim Society, 9(2), 77-92. doi:10.15408/tjems.v9i1. 29071.